Evaluation of clinical performance and survival rate of Straumann dental implants in Saudi Population based on cross-sectional study - Jasser, Reham AL (Sci Rep, 2021)
Risk indicators of peri-implantitis is still contradictory and somehow unclear in present literature therefore efforts should be done for better understanding of the exact etiology of peri-implant disease progression. The present study aimed to assess risk indicators associated with peri-implantitis by observing the changes in several periodontal parameters after implant placement. This cross-sectional study included 213 female and 271 male patients aged 26–87 years, who received 484 titanium implants (Straumann, Switzerland) at King Saud University’s Dental College, Saudi Arabia. Patients were called for dental visits. During these visits; full clinical and radiographic assessment of implants were done. The periodontal pocket depth (PPD) was greater around implants placed at grafted sites than non-grafted sites and around bone-level implants than tissue-level implants. The plaque index (PI) was associated with poor oral hygiene. There was a strong association between graft (yes/no) and bleeding on probing (BOP). Patients with good oral hygiene showed high radiographic bone stability. Keratinized tissue width < 2 mm was associated with a higher PPD, higher PI, higher BOP, more edematous gingiva, and more exposed implant threads on radiography. In patients receiving implants, poor oral hygiene status and inadequate keratinized tissue level can be proposed as risk indicators for developing periimplantitis due to strong association found between them and developments of peri-implantitis.